MANEJEMEN FISIOTERAPI PADA PENANGANAN THORACIC OUTLET SYNDROME (TOS) DENGAN MANUAL TERAPI: CASE REPORT - Nabila, Aulia Safa’; Adnan Faris Naufal; Melur Belinda (Journal of Innovation Research and Knowledge, 2024)
Thoracic outlet syndrome (TOS) is the compression of nerves and blood vessels in one area around the thorax. TOS is a complex group of symptoms including nerve disorders in the upper extremities, arterial disorders, and venous disorders. The prevalence of TOS according to the classification of 3 types: neurogenic TOS cases get 95-99%, venous TOS 3-5% and arterial TOS 1-2%. Other factors causing TOS include neck and shoulder trauma, postural problems, work-related injuries, and repetitive overhead activities. Purpose: In this study to determine the effect of physiotherapy interventions, namely manual therapy in the form of scapula mobiliation, scaleni stretching, and sternoclavicular mobilization. Methods: This study was conducted directly on 1 respondent with TOS patients for 3 therapy sessions. Result: After 3 therapy sessions, there was a decrease in pain, increased ROM, and improved functional abilities. Conclusion: There is an effect of physiotherapy management in the form of manual therapy on reducing pain, increasing ROM, and improving functional abilities.